Economic Analysis of Law And Its Application In Government Regulation No. 64 of 2021 On Land Bank Agency - Khafidzoh, Adiani Mutiara (Journal of Agri Socio Economics and Business, 2023)
The argument of law from various points of view has given birth to so many theories and concepts, one of the theories used in legal analysis is the Economic Analyis of Law. Between law and economics, both can be used as an analytical tool between economic impact and legal impact, and vice versa. Badan Bank Tanah is a sui generis legal entity established by the government through the Undang-Undang Cipta Kerja to support increased investment through the provision of land in the context of an equitable economy. All matters regarding the duties and functions of the Badan Bank Tanah are further regulated in Peraturan Pemerintah No. 64 Tahun 2021 about Badan Bank Tanah. This writing will describe the various economic theories used in the legal approach, especially in Peraturan Pemerintah No. 64 Tahun 2021, namely the Maximization, Equlibrium, Efficiency and Cost-Benefit theories. The Economic Approach Theory was chosen because this regulation was born on the basis of economic interests, with its various tasks and functions the Badan Bank Tanah aims to facilitate and shorten the process of acquiring land for investment activities by optimally utilizing state lands.